A Note on International Real Interest Rate Differentials - Mark, Nelson C. (The Review of Economics and Statistics, 1985)
Abstrac t-This note empirically examines the issue of real interest rate equalization across countries. The equality of real interest rates is implied by two frequently employed concepts of equilibrium in international asset (capital) and commodity markets and imposes certain time series restrictions on ex post real interest rates. Statistical tests of these restrictions strongly reject the hypothesis that real interest rates have been equal across countries.